Qualitative Psycholgy Nexus Vol. VIII: Epistemologies for Qualitative Research ... - Soini, Hannu; Kronqvist, Eeva-Liisa; Huber, Günter L.; Maxwell, Joseph; Kiegelmann, Mechthild; Gento, Samuel; Medina, Antonio; Pina, Jorge; Domínguez, María Concepción; Schweizer, Karin; Korte, Petra; Pavlovic, Jelena; et al. (Leibniz Institut für Psychologie (ZPID), 2011)
The 9th annual meeting of the Center for Qualitative Psychology was held in Northern Finland, near to the city of Oulu. The seminar was started with two crucial questions leading the participants to the theme of the conference. The orientation followed the line of the former meetings of the Center for Qualitative Research in Psychology helping participants to reflect own ways of doing psychological research. In the beginning of the conference we asked the conference participants a simple question: What do you want to know about epistemology? In small groups the participants expressed questions like - what is epistemology, are there many epistemologies, what do we mean by epistemology and what epistemological approaches do we have in psychology. During the two conference days these questions we reformulated and new themes were elaborated by the participants. At the end of the seminar the participants were finally asked "in what questions did you find answers?" This volume presents articles on four extensive ...